Assessing drywell designs for managed aquifer recharge via canals and repurposed wells - Salini Sasidharan; Scott A. Bradford (Scientific Reports)
Abstract This study explores innovative drywell designs for managed aquifer recharge (MAR) in agricultural settings, focusing on smaller diameter and deeper drywells, including the repurposing of dried or abandoned wells. Numerical simulations assessed the impact of drywell diameter (5–120 cm), depth (15–55 m), screen height, and subsurface heterogeneity on infiltration (I) and recharge (R) volumes over a one-year period under constant head conditions. Results indicate that smaller diameter drywells can effectively infiltrate and recharge significant water volumes. A 5 cm diameter drywell exhibited only a 48% decrease in infiltration efficiency compared to a standard 120 cm drywell, while being easier to install and requiring less space. Deeper drywells substantially enhanced both I and R; a 20 cm diameter drywell at 55 m depth infiltrated 1.9 × 105 m3 and recharged 3.56 × 104 m3 within a year, with faster arrival times of recharge water. The study also proposes integrating drywells into existing irrigation canal networks. Simulations suggest that installing drywells every 70 m along canals could infiltrate 7.14 × 105 to 1.43 × 106 m3 of water per kilometer annually, significantly enhancing groundwater recharge in regions where traditional MAR methods are limited. Subsurface heterogeneity was found to increase I and R volumes compared to homogeneous conditions, emphasizing the importance of site-specific assessments. An economic analysis revealed that deeper, small-diameter drywells offer lower levelized costs, down to $0.46 per cubic meter of recharged water, making them economically viable alternatives. However, technical challenges such as clogging, water quality concerns, and regulatory requirements were identified. Pretreatment measures like sedimentation chambers and geotextile membranes are recommended to mitigate clogging, though their costs require further evaluation. Pilot-scale studies are recommended to validate simulation findings, assess technical and regulatory challenges, and refine designs for practical implementation.